Gorlin-Goltz syndrome: A rare case report - Chetan A Pol; Suvarna K Ghige; Ritesh R Kalaskar; Suchitra R Gosavi (Wolters Kluwer Medknow Publications, 2013)
Gorlin-Goltz syndrome is an uncommon autosomal dominant inherited disorder characterized by numerous basal cell carcinomas, odontogenic keratocysts (OKCs) and musculoskeletal malformations. A rare case of this syndrome observed in a 13-year-old male patient is presented in which multiple OKCs were causing disfigurement of the lower jaw as well as displacement and malocclusion of the teeth. Early diagnosis and treatment of this syndrome is important to reduce the severity of complications including cutaneous and cerebral malignancy and oromaxillofacial deformation and destruction due to jaw cysts.